2018
DOI: 10.1186/s12889-018-5116-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the use of contraceptives through the lens of teenage women: a qualitative study in Iran

Abstract: BackgroundOne out of seven teenage girls in developing countries marries before the age of 15. While the fertility rate of teenage girls is high, the rate of contraceptive use remains low; therefore, this group of teenagers needs reproductive healthcare. This study was undertaken to explore factors influencing the use of contraceptives from the perspective of teenage women living in the city of Ardabil in Iran.MethodsThis qualitative study was conducted with 14 married women aged 13–19 years who attended in ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 33 publications
9
36
0
Order By: Relevance
“…Consistent with previous studies [28,29], the study also revealed that those with poorest and poorer wealth quintiles were less likely to use modern contraceptives compared to those with richest wealth quintile. A study in Malawi also indicated that women in the highest wealth quintiles were more likely to use contraception as compared to those in the poorest income categories [29].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies [28,29], the study also revealed that those with poorest and poorer wealth quintiles were less likely to use modern contraceptives compared to those with richest wealth quintile. A study in Malawi also indicated that women in the highest wealth quintiles were more likely to use contraception as compared to those in the poorest income categories [29].…”
Section: Discussionsupporting
confidence: 89%
“…Evidence from Tanzania also indicated that unmarried-sexually active women who had reached the university level of education were three times more likely to use modern contraception compared with those with no education [5]. It has been argued that advancement in education has a potential role in shaping individuals' perceptions and knowledge about modern contraceptives, which aid them in overcoming misconceptions against modern contraception use [28]. Therefore the youth who were less educated had a lower chance of using modern contraceptives probably due to misconceptions [8].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that women who get married early have a weak position in family life and many life decisions are made by their husbands or even the husband's family. Research by Mardi et al also found that women who experienced early marriage were less independent in family life [17].…”
Section: Discussionmentioning
confidence: 93%
“…Irani & Latifnejad Roudsari, 2019 also showed in a review study that child marriage in girls is associated with the consequences of death during childbirth, physical and sexual violence, depression, risk of getting sexually transmitted diseases and preterm birth [16]. A qualitative study conducted by Mardi et al in 2018 in Ardabil, Iran, showed that adolescent women confront experiences such as misunderstanding of sexual relations, death of dreams and threatened independence. Also, the results of their study showed that adolescent women cannot understand life opportunities, and health care providers and policymakers need to make adolescents aware of the negative consequences of early marriage and prevent them from doing it [17].…”
Section: Nasrullah Et Al 2014 Entitled Child Marriage and Its Assocmentioning
confidence: 99%
“…There are many reported factors which have been shown to be meaningfully associated with the choice of contraceptive tools including fertility history, income, education and job, age and some of other demographic characteristics of women and their husbands (5). The present study was conducted to determine the most important socioeconomic and cultural factors which may be the reason behind choosing methods of contraception.…”
Section: Introductionmentioning
confidence: 98%